Boomers Like to Confront, Generation Y Is Okay with Withdrawal, But They All Love to Negotiate in India. (22nd March 2016) - Gupta, Priya; Bhattacharya, Sonali; Neelam, Netra; Kunte, Monika
Abstract : This article compares the conflict resolution styles of the three generations in the Indian workforce today—baby boomers, generation X, and generation Y—based on a research sample size of 503 respondents. The questionnaire developed by Pareek and Purohit (2010) classifies conflict resolution styles into five categories: three approach‐based styles (confrontation, compromise, and negotiation) and two avoidance‐based styles (withdrawal and resignation). The study found that Indian workers by and large prefer approach‐based styles, with negotiation being the most preferred style across generations and gender. Baby boomers were found to have a significantly higher preference for confrontation than those in generation Y. Generation Y is significantly more likely than baby boomers to choose withdrawal as their conflict resolution style. In addition, male baby boomers are more likely than female boomers to use resignation as a conflict resolution style. The article discusses possible reasons for these findings in the Indian cultural context and suggests future research.